Market Arrival Patterns and Price Volatility of Soybean in Indian Agricultural Markets: A Review - Priyanka Sudhakar Pardhi; Maan Singh Toor; Lovepreet Singh (Archives of Current Research International, 2025)
Soybeans, a fundamental crop for India’s agricultural sector, experience significant fluctuations in market arrivals and prices due to various factors, including climatic conditions, market dynamics, and policy interventions. This review demonstrates, through extensive data analysis, that price volatility is driven by domestic factors (such as local demand and supply) and international factors (such as global price trends and trade policies), as well as by rainfall patterns and farmers’ storage and financial capacities. Due to the impact that the COVID-19 pandemic has had on supply chains, the findings reveal periods of extreme unpredictability, particularly during the marketing period of 2021-2022. The review emphasizes the need for strategic interventions to stabilize the soybean market, such as expanding storage infrastructure, disseminating market information, and enacting policies to reduce the impact of global price fluctuations. These insights are crucial for policymakers, farmers, and various stakeholders aiming to manage risks and make informed decisions in the soybean market.